Reducing flood risk associated with basement drainage - Ladson, AR; Tilleard, J (Australian journal of water resources, 2013)
Basements in residential buildings are often subject to flooding. It is common practice to connect basement drainage by gravity to the stormwater system which means that if there is any surcharge caused by capacity constraint, constriction, blockage or partial blockage in the system downstream of where the basement drain connects then the basement is at risk of flooding. This surcharge can lead to water backing up in the drainage pipe and entering the basement. In this discussion paper we comment on flood risk from basement drainage, outline the current guidance and review possible safe drainage solutions. KEYWORDS: Flood risk; basement drainage.